Rape Prevention Through Bystander Education at a Northeastern State University, 2002-2004 - Banyard, Victoria L. ([Verlag nicht ermittelbar], 2008)
The purpose of the study was to evaluate the effectiveness of a rape prevention program that used a community of responsibility model to teach women and men how to intervene safely and effectively in cases of sexual violence before, during, and after incidents with strangers, acquaintances, or friends. Instead of focusing on women as potential victims and men as potential perpetrators, the program was different from other prevention programs in that it approached both women and men as potential bystanders or witnesses to behaviors related to sexual violence. Three hundred and eighty-nine undergraduate students were recruited to participant in the study in the spring (first wave) and fall (second wave) semesters of 2003 at a northeastern state university in the United States. Participants were randomly assigned to one of two treatment groups or a control group. All first-wave participants filled out pretest questionnaires (Part 1), post-test questionnaires (Part 2), and questionnaires two (Part 3) and twelve (Part 4) months following the first post test. Those in the first wave experimental conditions participated in the one-session or three-session training program prior to filling out the post-test questionnaire, and they participated in a booster session before filling out the questionnaire at the two-month mark. Second-wave participants experienced similar treatments through the two-month follow-up questionnaire. After that, they received a four-month follow-up questionnaire (Part 5) at the same time that the first-wave participants did their twelve-month follow-up questionnaire. Numerous demographic variables are included in the study, along with variables from 15 different scales, a knowledge questionnaire, responses to vignettes, and respondents' own experiences with sexual violence.